1999
DOI: 10.1055/s-2008-1043793
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic Transplant Potential of Unrelated and Related Cord Blood: The first six Years of the EUROCORD/NETCORD Bank Germany

Abstract: To date, human umbilical cord blood (CB) has been employed successfully in well over 1000 allogeneic (unrelated and sibling) stem cell transplantations. Because of primary limitations in volume and cell numbers, over 90% of these transplantations were performed in children. Therefore requests for well standardised cord blood units of high quality are now increasing constantly. Examination and standardisation of unrelated and related cord blood stem cell preparations and banking as well as their biological char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 10 publications
1
12
0
3
Order By: Relevance
“…4,7 In accordance with these findings, many UCB banks have established a policy of selecting units with high numbers of total nucleated and CD34 + cells. 8,9 Studies performed on healthy pregnancies have shown that gestational and obstetric factors, including maternal age, parity, gestational age, length of labor, stress during labor, route of delivery, technique of UCB collection and positioning of the newborn after delivery can influence the numbers of HSC in UCB obtained after delivery.…”
Section: Introductionmentioning
confidence: 97%
“…4,7 In accordance with these findings, many UCB banks have established a policy of selecting units with high numbers of total nucleated and CD34 + cells. 8,9 Studies performed on healthy pregnancies have shown that gestational and obstetric factors, including maternal age, parity, gestational age, length of labor, stress during labor, route of delivery, technique of UCB collection and positioning of the newborn after delivery can influence the numbers of HSC in UCB obtained after delivery.…”
Section: Introductionmentioning
confidence: 97%
“…In 1989, the first CB transplantation was reported in a boy suffering from Fanconi anemia; the first two series of CB transplantation from related and unrelated donors were reported in 1994 and 1995 [for review see 5]. The first unrelated CB banking programs were started in 1992 at the Eurocord/Netcord Bank in Düsseldorf [6] and in 1993 at the New York Blood Center [7].…”
mentioning
confidence: 99%
“…In Deutschland vertritt die Nabelschnurblutbank Düsseldorf NETCORD. Im Zeitraum von 1996 ± 1999 erhielt sie 4860 vorläufige Suchanfragen [5].…”
unclassified